2014
DOI: 10.1057/ap.2014.33
|View full text |Cite
|
Sign up to set email alerts
|

Issue emergence and the dynamics of electoral competition around immigration in Spain

Abstract: ABSTRACT:This article examines the changing dynamics of electoral competition around an increasingly salient issue in Spanish politics: immigration. We argue that, although the issue is close to a 'valence' one in terms of the views of the electorate, the behaviour of the three main state-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
0
16
0
6
Order By: Relevance
“…Echoing parties of a similar ideological and populist flare such as France’s Front National , Germany’s Alternative für Deutschland , Britain’s UKIP, and others across Europe (Art, 2011; Zhirkov, 2014), the party adopts a very hard line on immigration, advocating for the deportation of all undocumented immigrants, the deportation of those who commit any crime, and an end to social policies that serve to attract immigrants (Vox, 2018). The hard-line stance on immigration breaks away from the rest of the parties operating within Spain 4 (Morales et al, 2015) and the lack of political saliency traditionally given to the issue in public discourse and amongst voters (Encarnación, 2004).…”
Section: Voxmentioning
confidence: 99%
“…Echoing parties of a similar ideological and populist flare such as France’s Front National , Germany’s Alternative für Deutschland , Britain’s UKIP, and others across Europe (Art, 2011; Zhirkov, 2014), the party adopts a very hard line on immigration, advocating for the deportation of all undocumented immigrants, the deportation of those who commit any crime, and an end to social policies that serve to attract immigrants (Vox, 2018). The hard-line stance on immigration breaks away from the rest of the parties operating within Spain 4 (Morales et al, 2015) and the lack of political saliency traditionally given to the issue in public discourse and amongst voters (Encarnación, 2004).…”
Section: Voxmentioning
confidence: 99%
“…While parties do not greatly politicize immigration in their electoral manifestos, where they do, they tend to take extensive/positive stances (rather than restrictive/negative ones). This suggests that the rainbow nation tends to be extended to include immigrants, akin to what Morales et al (2015) observed in Spain. In addition to generally extensive or positive positions, we also observed a focus on immigrant integration (rather than immigration control), and instrumental justifications (rather than identity or norms).…”
Section: Discussionmentioning
confidence: 87%
“…It can easily be expected that this inclusive narrative extends to immigrants like to other groups in society. Studying the politicization of immigration in Spain, Morales et al (2015) highlight that such an extension of inclusiveness is possible, in their case during a period of economic hardship. Hiers et al (2017) highlight that countries with ethnic (rather than civic) forms of nationalism tend to come with stronger antiimmigrant sentiments.…”
Section: Introductionmentioning
confidence: 99%
“…Between agenda-setting and issue framing Over the past decades, scholars have investigated the politicization of immigration, looking at the way it has gained importance in both public and political discourse and shedding light on the many facets of this issue. 3 Political actors strategically select and emphasize different immigration-related topics within political and public debates (Buonfino, 2004;Vaccari, 2010;Fryberg et al, 2012;Kriesi et al, 2012;Ruedin and Berkhout, 2012;Colombo, 2013;Helbling, 2013;Morales et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This is particularly evident in the Italian political debate (Riva et al, 2008). As a highly contested issue (Boswell, 2003;Morales et al, 2015) in a new country of destination, immigration 4…”
Section: Introductionmentioning
confidence: 99%